"Getting There": Transportation as a Barrier to Research Participation Among Older Adults. (May 2022) - Rigatti, Madeline; DeGurian, Amy A.; Albert, Steven M.
Recruiting from a large university registry of older adults who have consented to be contacted for research, the Getting There study ( n = 500) asked about willingness to participate in research and obstacles posed by transportation. In the period before the pandemic (12/2019–3/2020), 88% of participants in the community registry were willing to travel to the research site. Driving and living closer to the research site, with better access to public transportation, were associated with significantly greater willingness to come to the medical center for research even after adjustment for age, difficulty getting in and out of a vehicle, and number of days leaving one's home each week. A qualitative inquiry drawing on a long-term care registry ( n = 23) showed a similar role for transportation challenges. Findings suggest transportation challenges among older people are a major source of unwillingness to participate in research even among highly motivated people participating in research registries.